Permeability Evaluation of 45S5 Bioglass Macroporous Scaffolds for Bone Tissue Engineering - Macías Andrés, V. I.; Orozco Sixtos, J. M.; Maldonado Paleo, J.; Aguilar Reyes, E. A. (Revista Mexicana de Ingenieria Biomedica, 2017)
Bioactive glass 45S5 foams were produced as an alternative to be used to fill and restore bone deffects. A crucial design factor of foams is permeability, since it is related to their capability for waste removal and nutrients/oxygen supply to cells. In the present work a study was carried out to analyze the bioactive glass 45S5 foams permeability by Darcy’s law. The measure average permeability value on foams of 69-74 % porosity was 4.19 × 10-10, 3.75 × 10-10 and 3.48 × 10-10 m2, which are in the range of permeability values for trabecular bone.